The impact of entrepreneurship, learning organization, organizational flexibility, and customer orientation on service quality: a study among IBII Jakarta lecturers - Ikhsan Ikhsan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
As higher education institutions strive to deliver excellence, it is imperative to identify the key factors that can drive improvements in service quality and empower institutions to meet the evolving needs of students and stakeholders. The objective of this research is to obtain information concerning the effect of entrepreneurship, organizational flexibility, learning organization and customer orientation on the service quality of higher education. This study was conducted in The Indonesian Institute of Business and Informatics (IBII) by using survey method with path analysis applied in testing hypothesis. The number of 60 founded lectures as a sample is selected by simple random sampling. The research findings are as follows: entrepreneurship has a direct impact on organizational learning, customer orientation, and the quality of higher education services. Organizational flexibility also directly influences these three aspects. However, there is no direct impact of organizational learning on customer orientation. Customer orientation has a direct impact on the quality of higher education services. The result of this research could imply that in developing and empowering the service quality of higher education, entrepreneurship, organizational flexibility, learning organization and customer orientation should be taken into account.